UV composite coating base film and preparation method thereof
By using the UV composite coating base film in a liquid crystal display and using the light diffusion layer composed of specific raw materials, the problem of difficult balance of the existing diffusion film haze and light transmittance is solved, and the dispersion and wear resistance of the film are improved , meet the high-performance needs of LCD displays.
Patent Information
- Application Number
- CN202310358833.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-04-06
AI Technical Summary
The conventional diffusing film is difficult to balance haze and light transmittance, and the dispersion of the light diffusing agent in the resin is poor, which affects the stability and quality of the diffusing film.
UV composite coating base film, including the base film and a light diffusion layer coated on the surface of the base film, is composed of polyurethane acrylate, light diffusion agent, photoinitiator, antioxidant, reactive diluent and adhesion The accelerator is composed of a specific raw material ratio and process to form a light diffusion layer with a tight structure, improving dispersion and wear resistance.
The light diffusion film is balanced in haze and light transmittance, which improves the wear resistance and durability of the film, and meets the high performance requirements of liquid crystal displays.
Smart Images

Figure BDA0004164276320000121 
Figure BDA0004164276320000131
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of optical films, and more specifically, to a UV composite coating base film and a preparation method thereof. Background Art
[0002] With the development of economy and technology, digitalization has become the trend of the times. Liquid crystal display (LCD) has become the most commonly used display technology. LCD has the advantages of green environmental protection, low energy consumption, low radiation, and soft picture. Liquid crystal display is generally composed of liquid crystal panel and backlight module. The backlight module mainly includes components such as light source, reflective film, light guide plate, diffusion film, brightness enhancement film and frame. Among them, the main function of the diffusion film is to enhance the brightness of light and evenly convert the light source or point light source into a surface light source. Its working principle is to use light passing through media with different refractive indices, and the light produces many refraction, reflection and scattering phenomena, which can improve the viewing angle, increase the softness of the light source, achieve optical diffusion effect, and also have the function of protecting the prism.
[0003] At present, the diffusion film is mainly a composite film of a light diffuser and a resin. Multiple scattering occurs between the light diffusers. This type of diffusion film usually shows high haze but low transmittance. In addition, the light diffuser has poor dispersibility in the resin and is prone to agglomeration, which affects the stability and quality of the diffusion film. Therefore, it is urgent to propose a UV composite coating base film and a preparation method thereof so that the diffusion film can achieve a balance between haze and transmittance, have excellent comprehensive performance, and meet the high performance requirements of liquid crystal displays. Summary of the invention
[0004] In order to solve the problem of poor quality of existing diffusion films due to the unbalanced haze and transmittance, the present application provides a UV composite coating base film and a preparation method thereof.
[0005] In a first aspect, the present application provides a UV composite coated base film, which adopts the following technical solution: the UV composite coated base film comprises a base film and a light diffusion layer coated on the surface of the base film;
[0006] The light diffusion layer comprises the following raw materials in parts by weight: 80-100 parts of polyurethane acrylate, 6-15 parts of light diffuser, 1.2-2.8 parts of photoinitiator, 2-3 parts of antioxidant, 21-28 parts of active diluent, and 0.2-0.8 parts of adhesion promoter;
[0007] The light diffuser comprises the following raw materials in parts by weight: 11-15 parts of composite microspheres, 4-7 parts of vinyl trimethoxy silane, 8-12 parts of sorbic acid, 1-2 parts of dibenzoyl peroxide, 40-60 parts of water, 4.1-5.3 parts of eight-arm hydroxybutyl cage-type polysilsesquioxane, and 20-30 parts of tetrahydrofuran.
[0008] By adopting the above-mentioned technical scheme, the coated base film of the present application includes a base film and a light diffusion layer coated on the base film, and the raw materials of the light diffusion layer include polyurethane acrylate, light diffuser, photoinitiator, antioxidant, active diluent, and adhesion promoter. The components interact with each other to form a tightly structured light diffusion layer, so that the coated base film can achieve a balance between haze and transmittance, has good wear resistance, and is durable. It is a light diffusion film with excellent performance and can be widely used in liquid crystal displays.
[0009] In addition, the light diffuser of the present application uses composite microspheres, vinyl trimethoxysilane, sorbic acid, dibenzoyl peroxide, eight-arm hydroxybutyl cage-type polysilsesquioxane, etc. as raw materials. The eight-arm hydroxybutyl cage-type polysilsesquioxane has both hydrophilic groups and lipophilic groups, and can be grafted to the surface of the composite microspheres through reaction, so that the composite microspheres have excellent dispersibility; when the light diffuser is added to the light diffusion layer, the octahedral cage structure of the eight-arm hydroxybutyl cage-type polysilsesquioxane can not only increase the porosity of the light diffusion layer, allowing more light to pass through and improve the light transmittance of the light diffusion layer; but also can increase the number of refractions of light and improve the haze of the light diffusion layer; in addition, the eight-arm hydroxybutyl cage-type polysilsesquioxane can also enable the light diffuser to have a cross-linking function, can react with polyurethane acrylate, and improve the wear resistance and mechanical properties of the light diffusion layer.
[0010] Preferably, the composite microspheres include the following raw materials in parts by weight: 10-20 parts of organosilicon microspheres, 40-60 parts of ethylenediaminetetraacetic acid solution, 4-8 parts of zinc chloride, 1-2 parts of sophorolipids, 3-4 parts of polyethylene glycol, 4-6 parts of sodium carbonate, and 0.5-1.5 parts of dimethylaminosulfonyl chloride.
[0011] Preferably, the composite microspheres are prepared by the following method:
[0012] S11, adding the organosilicon microspheres to the ethylenediaminetetraacetic acid solution, heating to 70-80° C., stirring and reacting for 30-60 minutes to obtain an organosilicon microsphere suspension;
[0013] S12, adding zinc chloride, sophorolipids, polyethylene glycol, sodium carbonate, and dimethylaminosulfonyl chloride to the organosilicon microsphere suspension obtained in step S11, and ultrasonically dispersing the mixture evenly; heating the mixture to 105-110° C. under nitrogen protection, reflux for 4-6 hours, and then filtering, washing, and drying to obtain composite microspheres.
[0014] Preferably, the ethylenediaminetetraacetic acid solution is obtained by mixing ethylenediaminetetraacetic acid and water in a volume ratio of 3-7:100.
[0015] By adopting the above technical scheme, the present application first uses ethylenediaminetetraacetic acid to treat the organosilicon microspheres, so that active groups are generated on the surface of the organosilicon microspheres, and then uses sophorolipids and polyethylene glycol, which work synergistically to induce zinc ions to grow on the surface of the organosilicon microspheres. A coating layer of nano zinc oxide is formed on the surface of the organosilicon microspheres, and the surface is rough, so that the composite microspheres have significant light diffusion performance; at the same time, the nano zinc oxide can also block ultraviolet rays and blue light, effectively making up for the defects of the organosilicon microspheres; in the preparation process of the composite microspheres, the present application controls various process parameters, so that the comprehensive performance of the composite microspheres is more excellent.
[0016] Preferably, the light diffusing agent is prepared by the following method:
[0017] S21, first add the composite microspheres and vinyl trimethoxysilane into water, adjust the pH to 3-3.5, heat to 70-80°C for reaction for 1.5-2.5h, then add sorbic acid and dibenzoyl peroxide, keep the same temperature for reaction for 2-3h, filter, and obtain carboxylated composite microspheres;
[0018] S22, dissolving the eight-arm hydroxybutyl cage-type polysilsesquioxane in tetrahydrofuran, adding the carboxylated composite microspheres obtained in step S21, adjusting the pH to 1-2, reflux reacting at 70-80° C. for 3-4 hours under nitrogen protection, filtering, and drying to obtain a light diffusing agent.
[0019] By adopting the above technical scheme, the present application performs carboxyl modification on the surface of the composite microspheres, introduces double bonds on the surface of the nano zinc oxide, and utilizes the double bonds on the surface to undergo a free radical polymerization reaction with sorbic acid under the initiation of dibenzoyl peroxide to obtain carboxylated composite microspheres; subsequently, the carboxyl groups of the composite microspheres undergo an esterification reaction with the hydroxyl groups of the eight-arm hydroxybutyl cage-type polysilsesquioxane, so that the eight-arm hydroxybutyl cage-type polysilsesquioxane is successfully grafted onto the surface of the composite microspheres, thereby greatly improving the dispersibility of the light diffuser and thereby improving the overall quality of the light diffusion layer.
[0020] Preferably, the antioxidant is obtained by mixing caffeic acid and apple phenol in a mass ratio of 4:3-7.
[0021] By adopting the above technical scheme, the antioxidant of the present application is obtained by mixing caffeic acid and apple phenol in a specific mass ratio. The two synergistically enhance each other. While improving the antioxidant performance of the light diffusion layer, it can also undergo a cross-linking reaction with polyurethane acrylate to increase the cross-linking density of the light diffusion layer and enhance the mechanical properties of the light diffusion layer.
[0022] Preferably, the photoinitiator is obtained by mixing benzoin ethyl ether and 2,4-dihydroxybenzophenone in a mass ratio of 2-6:5.
[0023] By adopting the above technical solution, the present application uses a mixture of benzoin ethyl ether and 2,4-dihydroxybenzophenone in a specific mass ratio as a photoinitiator. The interaction between the two significantly improves the photocuring rate and curing effect, thereby obtaining a light diffusion layer with excellent performance.
[0024] Preferably, the reactive diluent is tripropylene glycol diacrylate.
[0025] By adopting the above technical solution, the active diluent of the present application is tripropylene glycol diacrylate, which can not only reduce the viscosity of the system, but also participate in the photocuring reaction, so that the performance of the light diffusion layer is better.
[0026] Preferably, the adhesion promoter is adhesion promoter PN-702.
[0027] By adopting the above technical solution, the present application selects the adhesion promoter PN-702, so that the light diffusion layer can be firmly attached to the surface of the base film, so that the mechanical properties of the coated base film are significantly enhanced.
[0028] Preferably, the base film has a thickness of 45-60 μm; and the light diffusion layer has a thickness of 8-10 μm.
[0029] By adopting the above technical solution, the present application controls the thickness of the base film and the light diffusion layer within a certain range, which can effectively ensure that the coated base film has excellent mechanical properties while also having significant light diffusion performance.
[0030] In a second aspect, the present application provides a method for preparing a UV composite coating base film, using the following technical solution: The method for preparing a UV composite coating base film comprises the following steps:
[0031] S1. Mix polyurethane acrylate, light diffuser, photoinitiator, antioxidant and active diluent, and stir evenly to obtain light diffusion layer coating;
[0032] S2. Under ultraviolet radiation, the light diffusion layer coating is coated on the base film, and is embossed using a die. After complete curing, the coating is demoulded to obtain a UV composite coated base film.
[0033] By adopting the above-mentioned technical scheme, the present application uses UV technology to shape and solidify the light diffusion layer coating, and forms a tightly structured light diffusion layer on the surface of the base film, which has the characteristics of fast curing, environmental protection, non-toxicity, and scratch resistance; the preparation method of the UV composite coated base film of the present application has simple steps, low cost, and is suitable for industrial production. The obtained UV composite coated base film has broad application prospects.
[0034] Preferably, one side surface of the base film is subjected to single-sided corona or plasma pretreatment.
[0035] By adopting the above-mentioned technical scheme, the present application uses corona or plasma pretreatment on the surface of the base film to generate active groups on the surface of the base film, and cooperates with the adhesion promoter to connect the base film and the light diffusion layer with chemical bonds, thereby enhancing the interaction force between the base film and the light diffusion layer and improving the mechanical properties of the coated base film.
[0036] In summary, this application has the following beneficial effects:
[0037] 1. The UV composite coated base film of the present application includes a base film and a light diffusion layer coated on the surface of the base film; the light diffusion layer includes raw materials such as polyurethane acrylate, light diffuser, photoinitiator, antioxidant, active diluent, adhesion promoter, etc., so that the UV composite coated base film has high transmittance and high haze, which can achieve a balance between transmittance and haze, and effectively improve the shortcomings of existing diffusion films.
[0038] 2. The light diffuser of the present application is nano zinc oxide loaded on the surface of silicone microspheres, organically combining the organic diffuser and the inorganic diffuser to form composite microspheres, so that the light diffuser has the advantages of both; at the same time, in order to make the light diffuser obtain excellent dispersion performance, eight-arm hydroxybutyl cage-type polysilsesquioxane is grafted on the surface of the composite microspheres, so that the light diffusion performance of the light diffuser is further improved; in addition, the light diffuser can also enhance the wear resistance of the coating base film, effectively extending the service life of the coating base film.
[0039] 3. The preparation method of the UV composite coating base film of the present application has simple steps and low cost, so that the coating base film not only has outstanding light diffusion performance, but also has significant mechanical properties, which can meet the high performance requirements of liquid crystal displays. DETAILED DESCRIPTION
[0040] The present application is further described in detail below in conjunction with embodiments.
[0041] Preparation Examples 1-5 and Comparative Preparation Examples 1-3 provide composite microspheres and preparation methods thereof.
[0042] Preparation Example 1
[0043] Composite microspheres, including the following raw materials: 100 g of organosilicon microspheres, 400 g of ethylenediaminetetraacetic acid solution, 40 g of zinc chloride, 10 g of sophorolipids, 30 g of polyethylene glycol, 40 g of sodium carbonate, and 5 g of dimethylaminosulfonyl chloride;
[0044] The ethylenediaminetetraacetic acid solution is obtained by mixing ethylenediaminetetraacetic acid and water in a volume ratio of 3:100;
[0045] Composite microspheres are prepared by the following method:
[0046] S11, adding the organosilicon microspheres to the ethylenediaminetetraacetic acid solution, heating to 70° C., stirring at a speed of 600 r / min for 60 min, to obtain an organosilicon microsphere suspension;
[0047] S12, adding zinc chloride, sophorolipids, polyethylene glycol, sodium carbonate, and dimethylaminosulfonyl chloride to the organosilicon microsphere suspension obtained in step S11, and ultrasonically dispersing for 10 minutes; heating to 105° C. under nitrogen protection, reflux reaction for 6 hours, and then filtering, washing, and drying to obtain composite microspheres.
[0048] Preparation Example 2
[0049] Composite microspheres, including the following raw materials: 120 g of organosilicon microspheres, 450 g of ethylenediaminetetraacetic acid solution, 50 g of zinc chloride, 12 g of sophorolipids, 33 g of polyethylene glycol, 45 g of sodium carbonate, and 8 g of dimethylaminosulfonyl chloride;
[0050] The ethylenediaminetetraacetic acid solution is obtained by mixing ethylenediaminetetraacetic acid and water in a volume ratio of 1:25;
[0051] Composite microspheres are prepared by the following method:
[0052] S11, adding the organosilicon microspheres to a 0.5% by mass ethylenediaminetetraacetic acid solution, heating to 72° C., stirring at a speed of 700 r / min for 50 min, to obtain an organosilicon microsphere suspension;
[0053] S12, adding zinc chloride, sophorolipids, polyethylene glycol, sodium carbonate, and dimethylaminosulfonyl chloride to the organosilicon microsphere suspension obtained in step S11, and ultrasonically dispersing for 12 minutes; heating to 106° C. under nitrogen protection, reflux reaction for 5.5 hours, filtering, washing, and drying to obtain composite microspheres.
[0054] Preparation Example 3
[0055] Composite microspheres, including the following raw materials: 150 g of organosilicon microspheres, 500 g of ethylenediaminetetraacetic acid solution, 60 g of zinc chloride, 15 g of sophorolipids, 35 g of polyethylene glycol, 50 g of sodium carbonate, and 10 g of dimethylaminosulfonyl chloride;
[0056] The ethylenediaminetetraacetic acid solution is obtained by mixing ethylenediaminetetraacetic acid and water in a volume ratio of 1:20;
[0057] Composite microspheres are prepared by the following method:
[0058] S11, adding the organosilicon microspheres to the ethylenediaminetetraacetic acid solution, heating to 75° C., stirring at a speed of 800 r / min for 45 min, to obtain an organosilicon microsphere suspension;
[0059] S12, adding zinc chloride, sophorolipids, polyethylene glycol, sodium carbonate, and dimethylaminosulfonyl chloride to the organosilicon microsphere suspension obtained in step S11, and ultrasonically dispersing for 15 minutes; heating to 108° C. under nitrogen protection, reflux reaction for 5 hours, filtering, washing, and drying to obtain composite microspheres.
[0060] Preparation Example 4
[0061] Composite microspheres, including the following raw materials: 180 g of organosilicon microspheres, 550 g of ethylenediaminetetraacetic acid solution, 70 g of zinc chloride, 18 g of sophorolipids, 37 g of polyethylene glycol, 55 g of sodium carbonate, and 12 g of dimethylaminosulfonyl chloride;
[0062] The ethylenediaminetetraacetic acid solution is obtained by mixing ethylenediaminetetraacetic acid and water in a volume ratio of 3:50;
[0063] Composite microspheres are prepared by the following method:
[0064] S11, adding the organosilicon microspheres to the ethylenediaminetetraacetic acid solution, heating to 78° C., stirring at a speed of 900 r / min for 40 min, to obtain an organosilicon microsphere suspension;
[0065] S12, adding zinc chloride, sophorolipids, polyethylene glycol, sodium carbonate, and dimethylaminosulfonyl chloride to the organosilicon microsphere suspension obtained in step S11, and ultrasonically dispersing for 18 minutes; heating to 109° C. under nitrogen protection, reflux reaction for 4.5 hours, filtering, washing, and drying to obtain composite microspheres.
[0066] Preparation Example 5
[0067] Composite microspheres, including the following raw materials: 200 g of organosilicon microspheres, 600 g of ethylenediaminetetraacetic acid solution, 80 g of zinc chloride, 20 g of sophorolipids, 40 g of polyethylene glycol, 60 g of sodium carbonate, and 15 g of dimethylaminosulfonyl chloride;
[0068] The ethylenediaminetetraacetic acid solution is obtained by mixing ethylenediaminetetraacetic acid and water in a volume ratio of 7:100;
[0069] Composite microspheres are prepared by the following method:
[0070] S11, adding the organosilicon microspheres to the ethylenediaminetetraacetic acid solution, heating to 80° C., stirring at a speed of 1000 r / min for 30 min, to obtain an organosilicon microsphere suspension;
[0071] S12, adding zinc chloride, sophorolipids, polyethylene glycol, sodium carbonate, and dimethylaminosulfonyl chloride to the organosilicon microsphere suspension obtained in step S11, and ultrasonically dispersing for 20 minutes; heating to 110° C. under nitrogen protection, reflux reaction for 4 hours, filtering, washing, and drying to obtain composite microspheres.
[0072] Comparative Preparation Example 1
[0073] Comparative Preparation Example 1 is the same as Preparation Example 1, except that an equal mass of water is used to replace the ethylenediaminetetraacetic acid solution.
[0074] Comparative Preparation Example 2
[0075] Comparative Preparation Example 2 is the same as Preparation Example 1, except that an equal mass of sophorolipids is used to replace polyethylene glycol.
[0076] Comparative Preparation Example 3
[0077] Comparative Preparation Example 3 is the same as Preparation Example 1, except that an equal amount of polyethylene glycol is used to replace the sophorolipid.
[0078] Preparation Examples 6-10 and Comparative Preparation Examples 4-8 provide light diffusing agents and preparation methods thereof.
[0079] Preparation Example 6
[0080] A light diffuser, comprising the following raw materials: 110 g of composite microspheres, 40 g of vinyl trimethoxy silane, 80 g of sorbic acid, 10 g of dibenzoyl peroxide, 400 g of water, 41 g of eight-arm hydroxybutyl cage-type polysilsesquioxane, and 200 g of tetrahydrofuran;
[0081] Wherein, the composite microspheres are prepared by Preparation Example 1;
[0082] Light diffuser, prepared by the following method:
[0083] S21, first add the composite microspheres and vinyl trimethoxysilane into water, adjust the pH to 3, heat to 70°C for reaction for 2.5h, then add sorbic acid and dibenzoyl peroxide, keep the same temperature for reaction for 3h, filter, and obtain carboxylated composite microspheres;
[0084] S22, dissolving the eight-arm hydroxybutyl cage-type polysilsesquioxane in tetrahydrofuran, adding the carboxylated composite microspheres obtained in step S21, adjusting the pH to 1 with dilute sulfuric acid, reflux reacting at 70° C. for 4 h under nitrogen protection, filtering, and drying to obtain a light diffusing agent.
[0085] Preparation Example 7
[0086] A light diffuser, comprising the following raw materials: 120 g of composite microspheres, 45 g of vinyl trimethoxy silane, 90 g of sorbic acid, 12 g of dibenzoyl peroxide, 450 g of water, 44 g of eight-arm hydroxybutyl cage-type polysilsesquioxane, and 200 g of tetrahydrofuran;
[0087] Wherein, the composite microspheres are prepared by Preparation Example 2;
[0088] Light diffuser, prepared by the following method:
[0089] S21, first add the composite microspheres and vinyl trimethoxysilane into water, adjust the pH to 3.2, heat to 72°C for reaction for 2.2h, then add sorbic acid and dibenzoyl peroxide, keep the same temperature for reaction for 2.8h, filter, and obtain carboxylated composite microspheres;
[0090] S22, dissolving the eight-arm hydroxybutyl cage-type polysilsesquioxane in tetrahydrofuran, adding the carboxylated composite microspheres obtained in step S21, adjusting the pH to 1.2 with dilute sulfuric acid, reflux reacting at 72° C. for 3.8 h under nitrogen protection, filtering, and drying to obtain a light diffusing agent.
[0091] Preparation Example 8
[0092] A light diffuser, comprising the following raw materials: 130 g of composite microspheres, 60 g of vinyl trimethoxy silane, 100 g of sorbic acid, 15 g of dibenzoyl peroxide, 500 g of water, 48 g of eight-arm hydroxybutyl cage-type polysilsesquioxane, and 250 g of tetrahydrofuran;
[0093] Wherein, the composite microspheres are prepared by Preparation Example 3;
[0094] Light diffuser, prepared by the following method:
[0095] S21, first add the composite microspheres and vinyl trimethoxysilane into water, adjust the pH to 3.3, heat to 75°C for reaction for 2 hours, then add sorbic acid and dibenzoyl peroxide, keep the same temperature and continue to react for 2.5 hours, filter, and obtain carboxylated composite microspheres;
[0096] S22, dissolving the eight-arm hydroxybutyl cage-type polysilsesquioxane in tetrahydrofuran, adding the carboxylated composite microspheres obtained in step S21, adjusting the pH to 1.5 with dilute sulfuric acid, reflux reacting at 75° C. for 3.5 h under nitrogen protection, filtering, and drying to obtain a light diffusing agent.
[0097] Preparation Example 9
[0098] A light diffuser, comprising the following raw materials: 140 g of composite microspheres, 60 g of vinyl trimethoxy silane, 110 g of sorbic acid, 18 g of dibenzoyl peroxide, 550 g of water, 50 g of eight-arm hydroxybutyl cage-type polysilsesquioxane, and 280 g of tetrahydrofuran;
[0099] Wherein, the composite microspheres are prepared by Preparation Example 4;
[0100] Light diffuser, prepared by the following method:
[0101] S21, first add the composite microspheres and vinyl trimethoxysilane into water, adjust the pH to 3.4, heat to 78°C for reaction for 1.8h, then add sorbic acid and dibenzoyl peroxide, keep the same temperature and continue to react for 2.3h, filter, and obtain carboxylated composite microspheres;
[0102] S22, dissolving the eight-arm hydroxybutyl cage-type polysilsesquioxane in tetrahydrofuran, adding the carboxylated composite microspheres obtained in step S21, adjusting the pH to 1.8 with dilute sulfuric acid, reflux reacting at 78° C. for 3.2 h under nitrogen protection, filtering, and drying to obtain a light diffuser.
[0103] Preparation Example 10
[0104] A light diffuser, comprising the following raw materials: 150 g of composite microspheres, 70 g of vinyl trimethoxysilane, 120 g of sorbic acid, 20 g of dibenzoyl peroxide, 600 g of water, 53 g of eight-arm hydroxybutyl cage-type polysilsesquioxane, and 300 g of tetrahydrofuran;
[0105] Wherein, the composite microspheres are prepared by Preparation Example 5;
[0106] Light diffuser, prepared by the following method:
[0107] S21, first add the composite microspheres and vinyl trimethoxysilane into water, adjust the pH to 3.5, heat to 80°C for reaction for 1.5h, then add sorbic acid and dibenzoyl peroxide, keep the same temperature for reaction for 2h, filter, and obtain carboxylated composite microspheres;
[0108] S22, dissolving the eight-arm hydroxybutyl cage-type polysilsesquioxane in tetrahydrofuran, adding the carboxylated composite microspheres obtained in step S21, adjusting the pH to 2 with dilute sulfuric acid, reflux reacting at 80° C. for 3 h under nitrogen protection, filtering, and drying to obtain a light diffusing agent.
[0109] Comparative Preparation Example 4
[0110] Comparative Preparation Example 4 is the same as Preparation Example 6, except that an equal mass of vinyltriethoxysilane is used to replace vinyltrimethoxysilane.
[0111] Comparative Preparation Example 5
[0112] Comparative Preparation Example 5 is the same as Preparation Example 6, except that an equal amount of methacrylic acid is used to replace sorbic acid.
[0113] Comparative Preparation Example 6
[0114] Comparative Preparation Example 6 is the same as Preparation Example 6, except that the composite microspheres are prepared by Comparative Preparation Example 1.
[0115] Comparative Preparation Example 7
[0116] Comparative Preparation Example 7 is the same as Preparation Example 6, except that the composite microspheres are prepared by Comparative Preparation Example 2.
[0117] Comparative Preparation Example 8
[0118] Comparative Preparation Example 8 is the same as Preparation Example 6, except that the composite microspheres are prepared by Comparative Preparation Example 3.
[0119] Examples 1-8 provide UV composite coating base films and preparation methods thereof.
[0120] Example 1
[0121] A UV composite coated base film, comprising a base film and a light diffusion layer coated on the surface of the base film;
[0122] The base film is made of PET film, and the light diffusion layer includes the following raw materials: 800g of polyurethane acrylate, 60g of light diffuser, 12g of photoinitiator, 20g of antioxidant, 210g of active diluent, and 2g of adhesion promoter;
[0123] Wherein, the light diffuser is prepared by Preparation Example 6; the photoinitiator is obtained by mixing benzoin ethyl ether and 2,4-dihydroxybenzophenone in a mass ratio of 2:5; the antioxidant is obtained by mixing caffeic acid and apple phenol in a mass ratio of 4:3; the active diluent is tripropylene glycol diacrylate; the adhesion promoter is adhesion promoter PN-702;
[0124] The method for preparing a UV composite coating base film comprises the following steps:
[0125] S0, performing single-sided corona pretreatment on one side surface of the PET film, with an output power of 1.5KW and a speed of 5m / min to obtain a pretreated PET film;
[0126] S1. Mix polyurethane acrylate, light diffuser, photoinitiator, antioxidant and active diluent, and stir at a speed of 600 r / min for 1 h to obtain a light diffusion layer coating;
[0127] S2, at a wavelength of 365nm and an intensity of 500mJ / cm 2 Under ultraviolet radiation, the light diffusion layer coating is coated on the pre-treated PET film with a thickness of 60 μm, the thickness of the light diffusion coating is 10 μm, and it is embossed using a stamping mold. After complete curing, it is demolded to obtain a UV composite coating base film.
[0128] Example 2
[0129] A UV composite coated base film, comprising a base film and a light diffusion layer coated on the surface of the base film;
[0130] The base film is PET film, and the light diffusion layer includes the following raw materials: 850g of polyurethane acrylate, 80g of light diffuser, 15g of photoinitiator, 23g of antioxidant, 23g of active diluent, and 4g of adhesion promoter;
[0131] Wherein, the light diffuser is prepared by Preparation Example 7; the photoinitiator is obtained by mixing benzoin ethyl ether and 2,4-dihydroxybenzophenone in a mass ratio of 3:5; the antioxidant is obtained by mixing caffeic acid and apple phenol in a mass ratio of 1:1; the active diluent is tripropylene glycol diacrylate; the adhesion promoter is adhesion promoter PN-702;
[0132] The method for preparing a UV composite coating base film comprises the following steps:
[0133] S0, performing single-sided corona pretreatment on one side surface of the PET film, with an output power of 2KW and a speed of 10m / min to obtain a pretreated PET film;
[0134] S1. Mix polyurethane acrylate, light diffuser, photoinitiator, antioxidant and active diluent, and stir at a speed of 700 r / min for 0.8 h to obtain a light diffusion layer coating;
[0135] S2, at a wavelength of 365nm and an intensity of 600mJ / cm 2 Under ultraviolet radiation, the light diffusion layer coating is coated on the pre-treated PET film with a thickness of 60 μm, the thickness of the light diffusion coating is 10 μm, and it is embossed using a stamping mold. After complete curing, it is demolded to obtain a UV composite coating base film.
[0136] Example 3
[0137] A UV composite coated base film, comprising a base film and a light diffusion layer coated on the surface of the base film;
[0138] The base film is made of PET film, and the light diffusion layer includes the following raw materials: 900g of polyurethane acrylate, 10g of light diffuser, 20g of photoinitiator, 25g of antioxidant, 250g of active diluent, and 5g of adhesion promoter;
[0139] Wherein, the light diffuser is prepared by Preparation Example 8; the photoinitiator is obtained by mixing benzoin ethyl ether and 2,4-dihydroxybenzophenone in a mass ratio of 4:5; the antioxidant is obtained by mixing caffeic acid and apple phenol in a mass ratio of 4:5; the active diluent is tripropylene glycol diacrylate; the adhesion promoter is adhesion promoter PN-702;
[0140] The method for preparing a UV composite coating base film comprises the following steps:
[0141] S0, performing single-sided corona pretreatment on one side surface of the PET film, with an output power of 4KW and a speed of 30m / min to obtain a pretreated PET film;
[0142] S1. Mix polyurethane acrylate, light diffuser, photoinitiator, antioxidant and active diluent, and stir at a speed of 800 r / min for 0.7 h to obtain a light diffusion layer coating;
[0143] S2, at a wavelength of 365nm and an intensity of 900mJ / cm 2 Under ultraviolet radiation, the light diffusion layer coating is coated on the pre-treated PET film with a thickness of 60 μm, the thickness of the light diffusion coating is 10 μm, and it is embossed using a stamping mold. After complete curing, it is demolded to obtain a UV composite coating base film.
[0144] Example 4
[0145] A UV composite coated base film, comprising a base film and a light diffusion layer coated on the surface of the base film;
[0146] The base film is PET film, and the light diffusion layer includes the following raw materials: 950g of polyurethane acrylate, 120g of light diffuser, 25g of photoinitiator, 28g of antioxidant, 260g of active diluent, and 7g of adhesion promoter;
[0147] Wherein, the light diffuser is prepared by Preparation Example 9; the photoinitiator is obtained by mixing benzoin ethyl ether and 2,4-dihydroxybenzophenone in a mass ratio of 1:1; the antioxidant is obtained by mixing caffeic acid and apple phenol in a mass ratio of 2:3; the active diluent is tripropylene glycol diacrylate; the adhesion promoter is adhesion promoter PN-702;
[0148] The method for preparing a UV composite coating base film comprises the following steps:
[0149] S0, performing single-sided corona pretreatment on one side surface of the PET film, with an output power of 5KW and a speed of 40m / min to obtain a pretreated PET film;
[0150] S1. Mix polyurethane acrylate, light diffuser, photoinitiator, antioxidant and active diluent, and stir at a speed of 900 r / min for 0.6 h to obtain a light diffusion layer coating;
[0151] S2, at a wavelength of 365nm and an intensity of 900mJ / cm 2 Under ultraviolet radiation, the light diffusion layer coating is coated on the pre-treated PET film with a thickness of 60 μm, the thickness of the light diffusion coating is 10 μm, and it is embossed using a stamping mold. After complete curing, it is demolded to obtain a UV composite coating base film.
[0152] Example 5
[0153] A UV composite coated base film, comprising a base film and a light diffusion layer coated on the surface of the base film;
[0154] The base film is made of PET film, and the light diffusion layer includes the following raw materials: 1000g of polyurethane acrylate, 150g of light diffuser, 28g of photoinitiator, 30g of antioxidant, 280g of active diluent, and 8g of adhesion promoter;
[0155] Wherein, the light diffuser is prepared by Preparation Example 10; the photoinitiator is obtained by mixing benzoin ethyl ether and 2,4-dihydroxybenzophenone in a mass ratio of 6:5; the antioxidant is obtained by mixing caffeic acid and apple phenol in a mass ratio of 4:7; the active diluent is tripropylene glycol diacrylate; the adhesion promoter is adhesion promoter PN-702;
[0156] The method for preparing a UV composite coating base film comprises the following steps:
[0157] S0, performing single-sided corona pretreatment on one side surface of the PET film, with an output power of 6.0KW and a speed of 50m / min to obtain a pretreated PET film;
[0158] S1. Mix polyurethane acrylate, light diffuser, photoinitiator, antioxidant and active diluent, and stir at a speed of 1000 r / min for 0.5 h to obtain a light diffusion layer coating;
[0159] S2, at a wavelength of 365nm and an intensity of 1000mJ / cm 2 Under ultraviolet radiation, the light diffusion layer coating is coated on the pre-treated PET film with a thickness of 60 μm, the thickness of the light diffusion coating is 10 μm, and it is embossed using a stamping mold. After complete curing, it is demolded to obtain a UV composite coating base film.
[0160] Example 6
[0161] Example 6 is the same as Example 1, except that: Step S0, one side surface of the PET film is subjected to single-sided plasma pretreatment with nitrogen at a plasma power of 0.05 kW.
[0162] Example 7
[0163] Example 7 is the same as Example 1, except that: Step S2, at a wavelength of 365 nm and an intensity of 500 mJ / cm 2 Under ultraviolet radiation, the light diffusion layer coating is coated on the pre-treated PET film with a thickness of 45 μm, the thickness of the light diffusion coating is 8 μm, and it is embossed using a stamping mold. After complete curing, it is demolded to obtain a UV composite coating base film.
[0164] Example 8
[0165] Example 8 is the same as Example 1, except that: Step S2, at a wavelength of 365 nm and an intensity of 500 mJ / cm 2Under ultraviolet radiation, the light diffusion layer coating is coated on the pre-treated PET film with a thickness of 50 μm, the thickness of the light diffusion coating is 9 μm, and it is embossed using a stamping mold. After complete curing, it is demolded to obtain a UV composite coating base film.
[0166] In order to verify the performance of the UV composite coating base film provided by the present application, the applicant set up comparative examples 1-13, wherein:
[0167] Comparative Example 1
[0168] Comparative Example 1 is the same as Example 1, except that the light diffusing agent is prepared by Comparative Preparation Example 4.
[0169] Comparative Example 2
[0170] Comparative Example 2 is the same as Example 1, except that the light diffusing agent is prepared by Comparative Preparation Example 5.
[0171] Comparative Example 3
[0172] Comparative Example 3 is the same as Example 1, except that the light diffusing agent is prepared by Comparative Preparation Example 6.
[0173] Comparative Example 4
[0174] Comparative Example 4 is the same as Example 1, except that the light diffusing agent is prepared from Comparative Preparation 7.
[0175] Comparative Example 5
[0176] Comparative Example 5 is the same as Example 1, except that the light diffusing agent is prepared from Comparative Preparation 8.
[0177] Comparative Example 6
[0178] Comparative Example 6 is the same as Example 1, except that the light diffusing agent is obtained by mixing nano zinc oxide and organic silicon microspheres in a mass ratio of 1:1.
[0179] Comparative Example 7
[0180] Comparative Example 7 is the same as Example 1, except that the light diffusing agent is silicone microspheres.
[0181] Comparative Example 8
[0182] Comparative Example 8 is the same as Example 1, except that the antioxidant is only caffeic acid.
[0183] Comparative Example 9
[0184] Comparative Example 9 is the same as Example 1, except that the antioxidant is only apple phenol.
[0185] Comparative Example 10
[0186] Comparative Example 10 is the same as Example 1, except that the photoinitiator is only benzoin ethyl ether.
[0187] Comparative Example 11
[0188] Comparative Example 11 is the same as Example 1, except that the photoinitiator is only 2,4-dihydroxybenzophenone.
[0189] Comparative Example 12
[0190] Comparative Example 12 is the same as Example 1, except that the adhesion promoter PN-702 is not added.
[0191] Comparative Example 13
[0192] Comparative Example 13 is the same as Example 1, except that the PET film is not subjected to the corona pretreatment of step S0.
[0193] The main properties of the UV composite coating base films in Examples 1-8 and Comparative Examples 1-13 were tested respectively, and the following result parameters were obtained, as shown in Table 1:
[0194] Refer to GB / T 2410-2008 "Determination of light transmittance and haze of transparent plastics" to test the light diffusion performance of UV composite coating base film;
[0195] The UV transmittance of the UV composite coating base film was tested using the LS110A handheld split transmittance meter; the wear resistance of the UV composite coating base film was tested with reference to HG / T 4303-2012 "Measurement Method for Abrasion Resistance of Surface Hardened Polyester Film";
[0196] The tensile fracture performance test of UV composite coating base film was carried out with reference to GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets".
[0197] Table 1:
[0198]
[0199]
[0200] It can be seen from the data shown in Table 1 above that the comprehensive performance of the UV composite coating base film obtained in Examples 1-8 of the present application is far superior to that of the UV composite coating base film obtained in Comparative Examples 1-13, with higher light transmittance and haze, lower ultraviolet transmittance, better wear resistance and tensile properties, and has broad application prospects.
[0201] It can be seen from Example 1 and Comparative Example 1 that the light diffuser of Example 1 is prepared by Preparation Example 6, and the composite microspheres are treated with vinyl trimethoxy silane before carboxylation. Compared with Comparative Example 1, which is treated with vinyl triethoxy silane, the transmittance and haze of the UV composite coating base film obtained in Example 1 are higher; this is mainly because vinyl trimethoxy silane has less steric hindrance than vinyl triethoxy silane, and when the composite microspheres are treated with vinyl trimethoxy silane, the carboxylation effect of the composite microspheres is better.
[0202] It can be seen from Example 1 and Comparative Example 2 that the light diffuser of Example 1 is prepared by Preparation Example 6, in which sorbic acid carboxylation composite microspheres are used. Compared with Comparative Example 2, which uses methacrylic acid, the performance of the UV composite coating base film obtained in Example 1 is better; sorbic acid contains a conjugated double bond structure, and its reaction activity is stronger than that of methacrylic acid, and it reacts with the composite microspheres treated with vinyltrimethoxysilane, and the hydroxylation effect is better.
[0203] It can be seen from Example 1 and Comparative Example 3 that the light diffuser of Example 1 is prepared by Preparation Example 6, the composite microspheres in Preparation Example 6 are prepared by Preparation Example 1, and the silicone microspheres in the composite microspheres are pretreated with an ethylenediaminetetraacetic acid solution, compared with Comparative Example 3, in which the silicone microspheres are untreated, and the haze and anti-ultraviolet performance of the UV composite coating base film obtained in Example 1 are better, indicating that the pretreated silicone microspheres are more conducive to the growth of nano zinc oxide.
[0204] It can be seen from Example 1 and Comparative Examples 4 and 5 that the light diffuser of Example 1 is prepared by Preparation Example 6, and the composite microspheres in Preparation Example 6 are prepared by Preparation Example 1, and sophorolipids and polyethylene glycol are added as templates. Compared with Comparative Examples 4 and 5, the comprehensive performance of the UV composite coating base film obtained in Example 1 is better, indicating that sophorolipids and polyethylene glycol synergistically enhance the growth effect of nano zinc oxide.
[0205] It can be seen from Example 1 and Comparative Examples 6 and 7 that the light diffuser of Example 1 is prepared by Preparation Example 6, and the silicone microspheres and nano zinc oxide are organically combined together. Compared with Comparative Examples 6 and 7, the UV composite coating base film obtained in Example 1 not only has good light diffusion performance, but also has significant wear resistance and mechanical properties.
[0206] It can be seen from Example 1 and Comparative Examples 8 and 9 that the antioxidant in Example 1 is obtained by mixing caffeic acid and apple phenol, and in Comparative Examples 8 and 9, the overall performance of the UV composite coating base film obtained in Example 1 is significantly improved.
[0207] It can be seen from Example 1 and Comparative Examples 10 and 11 that the photoinitiator of Example 1 is obtained by mixing benzoin ethyl ether and 2,4-dihydroxybenzophenone. In Comparative Examples 10 and 11, the comprehensive performance of the UV composite coating base film obtained in Example 1 is more excellent.
[0208] It can be seen from Example 1 and Comparative Examples 12 and 13 that in Example 1, an adhesion promoter is added and the PET film is subjected to corona pretreatment. Compared with Comparative Examples 12 and 13, the haze, transmittance and mechanical properties of the UV composite coating base film of the coating obtained in Example 1 are improved.
[0209] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. UV composite coating base film, characterized in that: It includes a base film and a light diffusion layer coated on the surface of the base film; The light diffusion layer comprises the following raw materials in parts by weight: 80-100 parts of polyurethane acrylate, 6-15 parts of light diffuser, 1.2-2.8 parts of photoinitiator, 2-3 parts of antioxidant, 21-28 parts of active diluent, and 0.2-0.8 parts of adhesion promoter; The light diffuser comprises the following raw materials in parts by weight: 11-15 parts of composite microspheres, 4-7 parts of vinyl trimethoxy silane, 8-12 parts of sorbic acid, 1-2 parts of dibenzoyl peroxide, 40-60 parts of water, 4.1-5.3 parts of eight-arm hydroxybutyl cage-type polysilsesquioxane, and 20-30 parts of tetrahydrofuran; The composite microspheres include the following raw materials in parts by weight: 10-20 parts of organosilicon microspheres, 40-60 parts of ethylenediaminetetraacetic acid solution, 4-8 parts of zinc chloride, 1-2 parts of sophorolipids, 3-4 parts of polyethylene glycol, 4-6 parts of sodium carbonate, and 0.5-1.5 parts of dimethylaminosulfonyl chloride; The composite microspheres are prepared by the following method: S11, adding the organosilicon microspheres to the ethylenediaminetetraacetic acid solution, heating to 70-80° C., and stirring at a speed of 1200 r / min for 30 min to obtain an organosilicon microsphere suspension; S12, adding zinc chloride, sophorolipids, polyethylene glycol, sodium carbonate, and dimethylaminosulfonyl chloride to the organosilicon microsphere suspension obtained in step S11, and uniformly dispersing by ultrasonication; heating to 105-110° C. under nitrogen protection, reflux reaction for 4-6 hours, and then filtering, washing, and drying to obtain composite microspheres; The light diffusing agent is prepared by the following method: S21, first add the composite microspheres and vinyl trimethoxysilane into water, adjust the pH to 3-3.5, heat to 70-80°C for reaction for 1.5-2.5h, then add sorbic acid and dibenzoyl peroxide, keep the same temperature for reaction for 2-3h, filter, and obtain carboxylated composite microspheres; S22, dissolving the eight-arm hydroxybutyl cage-type polysilsesquioxane in tetrahydrofuran, adding the carboxylated composite microspheres obtained in step S21, adjusting the pH to 1-2, reflux reacting at 70-80° C. for 3-4 hours under nitrogen protection, filtering, and drying to obtain a light diffusing agent.
2. The UV composite coating base film according to claim 1, characterized in that: The antioxidant is obtained by mixing caffeic acid and apple phenol in a mass ratio of 4:3-7.
3. The UV composite coating base film according to claim 1, characterized in that: The photoinitiator is obtained by mixing benzoin ethyl ether and 2,4-dihydroxybenzophenone in a mass ratio of 2-6:
5.
4. The UV composite coating base film according to claim 1, characterized in that: The thickness of the base film is 45-60 μm; the thickness of the light diffusion layer is 8-10 μm.
5. A method for preparing a UV composite coating base film according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Mix polyurethane acrylate, light diffuser, photoinitiator, antioxidant and active diluent, and stir evenly to obtain light diffusion layer coating; S2. Under ultraviolet radiation, the light diffusion layer coating is coated on the base film, and is embossed using a die. After complete curing, the coating is demoulded to obtain a UV composite coated base film.
6. The method for preparing a UV composite coating base film according to claim 5, characterized in that: One side surface of the base film is subjected to single-sided corona or plasma pretreatment.
